2021
DOI: 10.1007/s11356-021-15548-0
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors and decoupling analysis of carbon emissions in China’s manufacturing industry

Abstract: The manufacturing industry directly reflects national productivity, and it is also an industry with serious carbon emissions, which has attracted wide attention. This study decomposes the influential factors on carbon emissions in China's manufacturing industry from 1995 to 2018 into industry value added (IVA), energy consumption (E), fixed asset investment (FAI), carbon productivity (CP), energy structure (EC), energy intensity (EI), investment carbon intensity (ICI) and investment efficiency (IE) by Generali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 67 publications
(31 reference statements)
2
32
0
Order By: Relevance
“…In terms of the structure factor IS, the driving directions of various industries of the industrial structure (IS) were inconsistent, and different stages showed inconsistent effects. This corroborated with the research of Jin and Han ( 2021 ). When the value was positive, it indicated that changes in the industrial structure are not conducive to the reduction of the industries’ CEP.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of the structure factor IS, the driving directions of various industries of the industrial structure (IS) were inconsistent, and different stages showed inconsistent effects. This corroborated with the research of Jin and Han ( 2021 ). When the value was positive, it indicated that changes in the industrial structure are not conducive to the reduction of the industries’ CEP.…”
Section: Resultssupporting
confidence: 92%
“…In recent years, researchers conducted more in-depth discussions on the driving factors of industrial carbon emissions. Among them, energy consumption intensity was the main indicator for reducing carbon emissions (Jin and Han 2021 ), and the expansion of industrial scale was the leading force driving the increase in carbon emissions (Du et al 2018 ), and it was most significant in the power industry. Udemba et al ( 2020 ) found positive correlations between carbon emissions and energy consumption, foreign direct investment, and population in addition to economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2020, the total scale of China's digital economy reached CNY 39.2 trillion, accounting for 38.6% of GDP, with a growth rate of 8.2%, ranking second in the world [3]. From the perspective of digital industrialization infrastructure, it mainly includes 5G, integrated circuits, artificial intelligence, big data, cloud computing, blockchain, and other electronic information industries and the Internet, providing technical products and services for the digital economy.…”
Section: Measurement Of Digital Industry Level In Chinamentioning
confidence: 99%
“…As a major manufacturing country, China's manufacturing global value chain division status has also changed, facing opportunities and challenges. Therefore, accelerating the development of the digital economy is of great significance in enhancing the division of labor status of China's manufacturing global value chains (GVCs) [3].…”
Section: Introductionmentioning
confidence: 99%
“…An et al [9] constructed a DEA and grid search (DEA-GS) model from a cost perspective to understand emission-reduction characteristics and found that the carbon price for China's manufacturing industry should not exceed 200 RMB/t. Jin and Han [10] conducted a decoupling analysis of carbon emissions and industrial value-added to investigate the state of the manufacturing industry under "low carbon" and "economy" pressures.…”
Section: Introductionmentioning
confidence: 99%